2012
DOI: 10.1007/s00210-012-0755-x
|View full text |Cite
|
Sign up to set email alerts
|

Bladder selectivity of the novel β3-agonist ritobegron (KUC-7483) explored by in vitro and in vivo studies in the rat

Abstract: We performed in vitro and in vivo experiments to evaluate the pharmacological profile of ritobegron and its effects on the bladder in rats. β(3)-AR selectivity was assessed using CHO cells expressing various subtypes of the human β-adrenoceptor (AR). Effects on isolated organs were evaluated using the organ-bath method. Effects on intravesical pressure, heart rate, and mean blood pressure were evaluated in urethane-anesthetized rats. Ritobegron increased cAMP accumulation in a concentration-dependent manner in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 17 publications
2
17
1
Order By: Relevance
“…In two series of experiments performed with similar protocols but with bladder strips from Japanese and German patients, we have demonstrated that KUC-7322 is 0.7-1.0 log units less potent than the reference agonist isoproterenol but has a comparable efficacy. These findings are in line with findings for rat detrusor relaxation, where KUC-7322 also was slightly less potent but similarly efficacious as isoproterenol (Maruyama et al 2012). In rats, these in vitro findings translated into a dosedependent reduction of intravesicular pressure in anesthetized animals in vivo by ritobegron, the prodrug of KUC-7322 (Maruyama et al 2012).…”
Section: Detrusor Relaxation Findingssupporting
confidence: 87%
See 2 more Smart Citations
“…In two series of experiments performed with similar protocols but with bladder strips from Japanese and German patients, we have demonstrated that KUC-7322 is 0.7-1.0 log units less potent than the reference agonist isoproterenol but has a comparable efficacy. These findings are in line with findings for rat detrusor relaxation, where KUC-7322 also was slightly less potent but similarly efficacious as isoproterenol (Maruyama et al 2012). In rats, these in vitro findings translated into a dosedependent reduction of intravesicular pressure in anesthetized animals in vivo by ritobegron, the prodrug of KUC-7322 (Maruyama et al 2012).…”
Section: Detrusor Relaxation Findingssupporting
confidence: 87%
“…KUC-7322 is the active metabolite of ritobegron (also known as and was reported to be 301-and 32-fold selective for β3-AR over β1-AR and β2-AR for stimulation of cAMP formation by cloned human receptor subtypes; a similar selectivity profile was obtained by comparing its potency for relaxation of rat bladder as compared to rat atrium and myometrium (Maruyama et al 2012). In two series of experiments performed with similar protocols but with bladder strips from Japanese and German patients, we have demonstrated that KUC-7322 is 0.7-1.0 log units less potent than the reference agonist isoproterenol but has a comparable efficacy.…”
Section: Detrusor Relaxation Findingsmentioning
confidence: 88%
See 1 more Smart Citation
“…Before this study, we were apprehensive that an increase in exposure of KUC-7322 might affect ECG parameters such as the heart rate and QT interval because KUC-7322 is a weak b 1 -and b 2-adrenoceptors agonist, even though it is highly selective for the b 3 -adrenoceptor; the selectivity of KUC-7322 for b 1 -and b 2-adrenoceptors is 1/301 and 1/32, respectively, of that for the b 3 -adrenoceptor. 6 Although an increase in exposure and a decrease in clearance were observed following coadministration of probenecid, there were no clinically significant abnormal ECG changes in this study. Furthermore, there were no obvious differences in subjective/objective findings, vital signs (blood pressure, pulse rate, and temperature), physical examinations (body weight), and clinical laboratory values (hematology, blood chemistry, and urinalysis) between ritobegron alone and ritobegron in combination with probenecid.…”
Section: Discussioncontrasting
confidence: 47%
“…To measure the KUC-7322 concentrations, blood samples (2 mL per time) were collected in vacuum blood collection tubes containing ethylenediaminetetraacetic acid disodium salt, sodium fluoride, and heparin at the following times after administration of ritobegron: 0.25, 0.5, 1, 1.5, 2, 3, 4,6,8,12,14,24,36, and 48 hours. Blood samples were centrifuged (3000 rpm) at 4˚C for 10 minutes and separated.…”
Section: Sample Collectionmentioning
confidence: 99%